The effects of lower eyelid epiblepharon surgery on the meibomian glands - Seongmi Kim; Da Eun Yoon; Hyun Sun Jeon; Namju Kim (BMC Ophthalmology)
Abstract Background To investigate the morphological and functional changes of meibomian glands (MG) in pediatric patients who underwent surgery for lower eyelid epiblepharon. Methods A total of 176 eyes of 88 patients aged 19 and under (mean age: 8.9 ± 2.8 years old) who underwent bilateral lower eyelid epiblepharon correction surgery from May 2022 to April 2023 were included. Meibograde, lipid layer thickness (LLT), total blink rate, and corneal/refractive astigmatism were compared between pre- and 2 months postoperatively. Results There were no statistically significant changes in meibograde and LLT after surgery. The total blink rate was significantly decreased after surgery (p = 0.02). While corneal and refractive astigmatism showed no significant changes in total eyes, corneal astigmatism in eyes of high astigmatism of 2.0D or more subgroup exhibited a significant decrease postoperatively (p < 0.001). Conclusions Lower eyelid epiblepharon surgery in pediatric patients does not significantly alter the structure and function of the MG. Additionally, stabilizing the ocular surface through surgical correction may have beneficial effects on blink rate and corneal astigmatism. Although the long-term evaluation would be needed, we suggest that lower eyelid epiblepharon surgery could be performed without worrying about adverse effects on the MG.